Evaluasi Penggunaan Aplikasi Point of Sale Menggunakan Technology Acceptance Model pada UMKM - Evasaria Magdalena Sipayung; Cut Fiarni; Wawan (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2020)
Point of Sale (POS) application in MSMEs is used as a tool for making sales. La Fresa Farm uses POS Intuit QuickBooks Enterprise 2015 application. As long as this application is implemented, users need a fairly long interaction time. Seeing these problems, tools are needed to evaluate the use of the application. In this study, the evaluation model used is the Technology Acceptance Model (TAM). TAM describes the ease of use and usefulness variables as the first measuring variables that affect other variables to the actual to use variable. The ease of use variable is the interaction time, which is measured using Keystroke Level Model (KLM). The usefulness variable is measured by cognitive models. In this study, there are additional variables outside the TAM model, namely self-efficacy, timeliness, and complexity. The test was carried out by the POS Intuit QuickBooks Enterprise 2015, Moka, Pawon, and Olsera applications. The KLM test results showed that the fastest time was 89.8 seconds and the results of TAM evaluation on Moka showed that the results of the actual to use variable response had a positive response, so that the interest of users using Moka was quite high.